Glagolitic abecedaries of Lovran - Mateo Žagar (Zbornik Lovranšćine, 2014)
This comparative article discusses the importance and particularities of three Glagolitic abecedaries from the 15th century scratched onto wall paintings inside Church of St. George in Lovran. The article presents their typicalities and particularities in relation to other known engraved Glagolitic abecedaries, in particular the oldest one – Glagolitic abecedary of Roč from 12th century. Attention is payed to alphabetic system and relations to graphemic inventory that is to be expected at the time, to the forms of letters presented, their positioning in respect to concrete base. In doing so, more general textual particularities of this miniaturistic textual art will be considered.